Intuitive thinking skills & its role in research - Badi, Jamal Ahmed Bashier (2021)
Is intuition a source of Knowledge? 1. Al Imam Ali Bin Abi Talib. (Deep Understanding of text) 2. Al Imam Al Ghazali. (Prior Knowledge & Sincerity). 3. Al Imam Zarouq. (Interpreting text)